(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the analysis of the compliance of the substantive and organizational characteristics of criminology as an educational discipline of higher educational institutions of the Ministry of Internal Affairs of Ukraine with modern trends in the scientific support of law enforcement activities. Increasing the role of criminology is due to the reform of the National Police, the transition to a proactive paradigm of activity. The development of criminology itself is hampered by its excessive jurisdiction. It is proposed to separate criminology from criminal law and strengthen the sociological and psychological content of the discipline. The relationship between the concepts of "criminology" and "criminal analysis" is considered. Recommendations are provided for organizing the study of criminology in accordance with the requirements of the time.